Dalla sovranità alla convivialità: strategie di sopravvivenza agroalimentare in Sardegna - Fabio Parascandolo; Maurizio Fadda (Archivio Antropologico Mediterraneo, 2024)
Unlike other geographical contexts of the Mediterranean world characterised by continentality and intense trade interconnections, the island of Sardinia – particularly in its inland and mountainous areas – for millennia remained populated by rural communities that had to rely on their own strength to survive. This entailed the establishment of agropastoral systems of subsistence and collective self-management at the local level in the processing and use of natural resources, and in particular food. Finally, the agri-food situation profoundly changed after a long period of legal and agrarian transformations that began in the era of Savoy reformism and with the gradual affirmation of exogenous models of cash crop agriculture (primarily sheep farming). The 20th century was the decisive century of this radical transformation, and yet forms of rootedness to the land in settled and neighbourhood communities remained conspicuous on the island, especially in centres of less than 10,000 inhabitants. A general framing of the topic will be accompanied by a description of some models of food sovereignty initiatives that recover some ancient aspects of food “rootedness” (including Solid Purchasing Groups and a Food Consumption Cooperative established in Cagliari), reinterpreting it in current times. These and similar phenomena highlight relevant instances of equitable and responsible access to appropriate agri-food systems for improved social and environmental conditions.